(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The relevance of the selected research topic: conducting a survey about the consumption of energy drinks among people in the current rapidly developing world and providing information about the harmful and beneficial aspects of energy drinks. The demand for energy drinks among young people is increasing, because of this rapidly developing period, getting extra energy, sleeping less, and drinking more drinks are becoming more and more common.